A continuous juggle of invisible forces: How fatigued dialysis patients manage daily life. (May 2021) - van der Borg, Wieke E; Verdonk, Petra; de Jong-Camerik, Judith GA; Schipper, Karen; Abma, Tineke A
Dialysis patients commonly experience severe fatigue. Fatigue is known as an intrusive symptom strongly affecting perceived quality of life. A total of 23 interviews were conducted to explore how dialysis patients respond to fatigue symptoms and its consequences in daily life. A constructivist grounded theory approach guided data analysis and conceptualization of findings. Patients find themselves within a continuous decision loop, considering ones (physical) abilities and questioning ones normative beliefs and values. This inner process interacts with the outside world, and contains various ambiguities. Improved understanding of this demanding process could help to better address fatigue and positively contribute to the quality of life of dialysis patients.